Transcriptional Pathways in cPGI2-Induced Adipocyte Progenitor Activation for Browning - Bayindir, Irem; Babaeikelishomi, Rohollah; Kocanova, Silvia; Sousa, Isabel Sofia; Lerch, Sarah; Hardt, Olaf; Wild, Stefan; Bosio, Andreas; Bystricky, Kerstin; Herzig, Stephan; Vegiopoulos, Alexandros (Frontiers in Endocrinology, 2015)
De novo formation of beige/brite adipocytes from progenitor cells contributes to the thermogenic adaptation of adipose tissue and holds great potential for the therapeutic remodeling of fat as a treatment for obesity. Despite the recent identification of several factors regulating browning of white fat, there is a lack of physiological cell models for the mechanistic investigation of progenitor-mediated beige/brite differentiation. We have previously revealed prostacyclin (PGI2) as one of the few known endogenous extracellular mediators promoting de novo beige/brite formation by relaying beta-adrenergic stimulation to the progenitor level. Here we present a cell model based on murine primary progenitor cells defined by markers previously shown to be relevant for in vivo browning, including a simplified isolation procedure. We demonstrate the specific and broad induction of thermogenic gene expression by PGI2 signaling in the absence of lineage conversion, and reveal the previously unidentified nuclear relocalization of the Ucp1 gene locus in association with transcriptional activation. By profiling the time course of the progenitor response we show that PGI2 signaling promoted progenitor cell activation through cell cycle and adhesion pathways prior to metabolic maturation towards an oxidative cell phenotype. Our results highlight the importance of core progenitor activation pathways for the recruitment of thermogenic cells and provide a resource for further mechanistic investigation.